Karasaman sebagai Pendekatan dalam Menumbuhkan Pembelajaran Bermakna - Lutfia, Fariha; Zakiyyan, Faza; Marsha Khaerunisa, Denia; Fairuz Aulia Akbar, Siti; Anazah; Putri Yudistira, Chantika; Nurpadilah, Dila; Nurdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This community service activity aims to introduce and instill Sundanese culture through the KARASAMAN (Kaulinan Rakyat Sunda Sareng Pasar Amanah) program, implemented by all students of SDN 6 Nagrikaler and P3K students from UPI Purwakarta. This activity is carried out through a series of activities, including traditional Sundanese games, an introduction to traditional culinary arts, and traditional market practices, due to the fading of Sundanese culture among the younger generation. Furthermore, this activity supports the strengthening of local cultural education, namely the 7 Poè Atikan, a regional education program in Purwakarta. Thus, KARASAMAN is able to provide a more enjoyable and meaningful learning experience and strengthen efforts to preserve Sundanese culture in elementary schools.